Contemporary Applications Of Artificial Intelligence In English Language Teaching: A Review Of Current Research And Empirical Evidence - Kamola Omonova (International Journal Of Literature And Languages, 2025)
Artificial Intelligence (AI) has emerged as a transformative force in English Language Teaching (ELT), reshaping instructional approaches, learner engagement and assessment practices across diverse educational contexts. This article provides a comprehensive review of contemporary AI applications in ELT, synthesizing empirical evidence and conceptual insights from recent systematic reviews and empirical studies. Drawing from the latest research on generative AI, intelligent tutoring systems, natural language processing tools, virtual agents and adaptive learning platforms (e.g., Lee et al., 2025; Kundu & Bej, 2025; Lo et al., 2024), the review evaluates trends, outcomes, challenges and pedagogical implications. Findings demonstrate consistent improvements in language proficiency, motivation, autonomy, feedback quality and engagement across speaking, writing, reading and vocabulary domains. However, issues related to digital inequity, teacher readiness, ethical use, cognitive load and contextual adaptability persist. The study proposes a holistic model of AI-enhanced ELT grounded in cognitive, sociocultural and pedagogical perspectives and offers recommendations for research, policy and classroom practice. This review contributes to ongoing debates about AI’s role in education and provides a consolidated evidence base for stakeholders seeking to integrate AI responsibly and effectively in English language education.